Pemanfaatan Limbah Kotoran Sapi Menjadi Pupuk Bokashi Organik di Desa Wongsorejo Kabupaten Banyuwangi - Aldy Bahaduri Indraloka; Eriko Romadian; Wifqi Izza Sulkhi; Devy Aprilia (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
Wongsorejo village have amount of agricultural and livestock potential. Livestock sector were able to produce cow waste product that can be used as a source of organic fertilizer. The survey results in agriculture potential, showed that the farmers of Wongsorejo Village were trying to switch to organic fertilizers and want to become an independent village of fertilizers. So the purpose of this PKM activity were the utilization of cow waste product into BOKASHI fertilizer as a source of organic fertilizer. This activity were divided into five stages, which were survey, socialization, training on making bokashi fertilizer, training on the mixer machine application and mentoring. PKM activities have a positive impact on the people of Wongsorejo Village, the community were able to produce fertilizer independently, the community gets a mixer machine for product efficiency and the community has a network and work organization in order to increase the fertilizer production.